Northeast Atlantic pelagic species catch statistics_2005-2016 - Viðarsson, Jónas R. (Zenodo, 2019)
Annualcatches of capelin, NSSH, NE Atlantic mackerel and blue whiting in the NE-Atlantic by country and catch area. Data used for developing climate adaptation plans within the ClimeFish project.